PENERAPAN METODE PEMBELAJARAN BRAINSTORMING DALAM MENINGKATKAN PENGETAHUAN CARING PADA MAHASISWA PROFESI NERS - Putri, Prestasianita; Susanti, Ika Adelia; Mardijanto, Said (FKIP Universitas Wisnuwardhana, 2023)
Caring is a core competence of nursing and becomes an essential aspect that should be developed among nurses including clinical nursing students. Caring behavior needs to be possessed by nursing students before entering health services. This community service activity aimed to increase the caring knowledge of clinical nursing students caring. There were three steps included in this activity such as preparation, implementation, and evaluation. Nursing students involved in this study were clinical nursing students in 2022 at Universitas dr. Soebandi. The first stage was defined by groups and the preparation of material on caring. The second stage was the implementation and education carried out on 30 students. Lastly was the evaluation using a questionnaire consisting of 10 questions related to carative factors based on Jean Watson's theory. The results showed that after giving education with brainstorming methods, there was an increase in knowledge about caring for clinical nursing students with a p-value of 0.000. It indicates the brainstorming method is effectively applied to improve understanding of cases in students of the ners profession. Therefore, it is recommended to adopt the brainstorming method in nursing education.